Integrated behavioral health services in pediatric primary care and emergency department utilization for suicide risk - Wellen, Brianna C. M.; Wright, Naomi M.; Bickford, Mira A.; Bakken, Eliza Hayes; Riley, Andrew R. (Frontiers in Psychiatry, 2023)
Introduction: Universal screening for suicide risk in primary care settings is a promising avenue for preventing self-harm and improving health outcomes. Triaging youth to an appropriate level of care, including diverting lower-risk patients from the emergency department (ED) is a meaningful goal. Previous research indicates integrated behavioral health (IBH) may prevent unnecessary admission to the ED on the day of suicide risk screening. We hypothesized that youth who received an IBH consultation the same day as suicide risk screening would be less likely to be admitted to the ED, but more likely to contact IBH services and utilize primary care in the following month. Methods: We conducted a retrospective chart review of 3,649 youth aged 10-18 years who were screened with the Ask Suicide-Screening Questions (ASQ) in two pediatric primary care practices. We collected demographic data, ASQ and Patient Health Questionnaire-9 (PHQ-9) scores, as well as patient medical contacts. We conducted a series of logistic regressions and chi-square analyses to determine whether contact with IBH on the same day as positive suicide risk screenings predicted same-day admission to the ED, IBH contact, and medical primary care utilization. Results: Among the 7,982 ASQ scores, 1,380 (18%) were non-acute and 87 ASQs (1%) screened acutely positive. Over 90% of positive screens were diverted from the ED regardless of IBH contact. Same-day IBH was associated with higher likelihood of general ED visits for all positive screens (acute and non-acute together). Contact with IBH the same day as screening positively predicted utilization of IBH and medical primary care services in the subsequent month, especially for youth with minority race and ethnicity identities. Discussion: In the context of clinics with IBH and systematic risk assessment processes, most youth who screen positive for suicide risk are diverted from the ED. However, our study showed that youth who received same-day IBH consultations were more likely to be admitted to the ED compared to peers who did not receive IBH consultations. These findings suggest that systematic suicide screening combined with IBH consultations in pediatric primary care can effectively identify risk levels and triage patients to appropriate care.